1983
DOI: 10.1007/bf00688389
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis myopathy

Abstract: Thirteen patients hemodialyzed for chronic renal insufficiency developed progressive paresis of the proximal musculature. Biopsies of the deltoid muscles of ten patients showed selective atrophy of type 2 fibers, the cause of which seems to be related to the osteomalacia present in those patients. Purification of the water for dialysis prior to the procedure prevents the muscle alteration: however, once the lesion is established only renal transplant will permit recovery of the muscle strength of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Since they studied biopsies of vastus lateralis, this discrepancy in fibre type distribution may be due to the confounding affect associated with disuse atrophy, resulting from reduced locomotory activity in the patients they studied. Most other studies of skeletal muscle morphology in renal failure have exclusively examined the locomotor muscle group, the quadriceps, in haemodialysis patients [2,[4][5][6][7][8][9][10]. Common findings in these studies, as in the present study, were of fibre atrophy, mostly of type IIa fibres, variation in fibre size and fibre type grouping.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Since they studied biopsies of vastus lateralis, this discrepancy in fibre type distribution may be due to the confounding affect associated with disuse atrophy, resulting from reduced locomotory activity in the patients they studied. Most other studies of skeletal muscle morphology in renal failure have exclusively examined the locomotor muscle group, the quadriceps, in haemodialysis patients [2,[4][5][6][7][8][9][10]. Common findings in these studies, as in the present study, were of fibre atrophy, mostly of type IIa fibres, variation in fibre size and fibre type grouping.…”
Section: Discussionmentioning
confidence: 60%
“…All previous studies of skeletal muscle morphology in renal failure have examined upper or lower limb (i.e. locomotor) muscle biopsies [4][5][6][7][8][9][10]. It is possible that the abnormalities observed may have been due both to the effects of uraemia and to disuse atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…These findings support the suggestion of a possible effect of ESRD/HD on the different components of the muscle motor-unit complex. Interestingly, Bautista et al 56 observed morphological characteristics suggestive of myopathy with no changes in electrophysiological characteristics, which implies that these changes could be present independently of each other. This finding may be attributed to the nature of the tools used and the status of the muscle during the test performed, given that EMG reflects muscle characteristics during activity whereas biopsy provides insight into muscle morphology at rest (Bautista et al 56 did not perform muscle biopsy during exercise).…”
Section: Discussionmentioning
confidence: 99%
“…The functional measures of strength reported in this study implicitly suggested muscle weakness, since the performance of the ESRD/HD group (age 54.5 e 2.6 years) on the 30-second chair-stand test (12 e 0.8 reps) was comparable to that of women between 75 and 79 years of age. 60 Of the four studies 15,16,55,56 that reported muscle weakness based on clinical assessments (measures not reported), two 15,55 suggested neuropathic changes preceding myopathic changes, based on the motor-unit recruitment pattern; one case series 16 observed myopathic changes; and the final study 56 observed EMG changes comparable to those observed in the control group.…”
Section: Electrophysiological Characteristicsmentioning
confidence: 99%
“…In a great or small degree of severity, atrophy of the muscle fibers was present in all biopsies of our cases, and muscle weakness and exhaustion to physical exercises were observed in these patients 11,[16][17][18][19] . Both patients and uremic animals are hypercatabolics, and in this process there is an involvement of the skeletal muscle which is a target tissue for catabolism and also for abnormal metabolism of the hormones (metabolites of vitamin D, PTH, insulin and catecholamines) associated with the so-called uremic myopathy 17,18,[20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%